2012
DOI: 10.1371/journal.pone.0037193
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Regulation of Zinc Uptake via ZIP Transporters in Yeast and Plant Roots

Abstract: In yeast (Saccharomyces cerevisiae) and plant roots (Arabidopsis thaliana) zinc enters the cells via influx transporters of the ZIP family. Since zinc is both essential for cell function and toxic at high concentrations, tight regulation is essential for cell viability. We provide new insight into the underlying mechanisms, starting from a general model based on ordinary differential equations and adapting it to the specific cases of yeast and plant root cells. In yeast, zinc is transported by the transporters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Up to now over 25 ZIP family transporters have been identified. On the basis of amino acid similarities, the respective genes fall into two subfamilies (Grotz et al 1998;Claus and Chavarría-Krauser 2012). The ZIP families of transporters are involved in the translocation of divalent cations across cellular membranes, and they are found in many plants, bacteria, fungi, and animal species.…”
Section: Zip Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now over 25 ZIP family transporters have been identified. On the basis of amino acid similarities, the respective genes fall into two subfamilies (Grotz et al 1998;Claus and Chavarría-Krauser 2012). The ZIP families of transporters are involved in the translocation of divalent cations across cellular membranes, and they are found in many plants, bacteria, fungi, and animal species.…”
Section: Zip Familymentioning
confidence: 99%
“…They were discovered on the basis of their similarity with IRT1 which is 54-65 %. Studies have demonstrated that normally yeast has two systems of Zn uptake (Claus and Chavarría-Krauser 2012). One system has high affinity and is activated only in Zn deficit cells, and the other has low affinity and is induced in cells with enough zinc.…”
Section: Zip Familymentioning
confidence: 99%
“…In Claus and Chavarría-Krauser (2012) we studied mathematical models for the regulation of ZIP transporters in response to external zinc concentration. The most promising model identified in this study included a dimerizing activator A, as well as an inhibitor I that senses the internal zinc concentration Z and inhibits the activator.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The parameter κ describes the induction of gene activity (u 1 ) by the dimerized activator (u 3 ), γ 1 and γ 3 the binding between activator and inhibitor (u 3 and u 4 ), γ 2 the binding between zinc (u 2 ) and the inhibitor (u 4 ), and K is the Michaelis constant of the reaction between external zinc (µ) and zinc transporters (u 1 ). All parameter values, here K = 13, κ = 20, γ 1 = 380, γ 2 = 1000, γ 3 = 1672, have been estimated from literature and by fitting the model to experimental data (Claus and Chavarría-Krauser, 2012). As a property of the soil, the external zinc concentration is considered as the bifurcation parameter µ ∈ M.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…A deterministic algorithm integrates the ODEs to produce a nonrandom solution [49]. The modelling of nutrient-centred biochemical pathways with the ODE approach has been extremely useful to the field of nutrition [50][51][52][53][54][55][56][57]. For instance, the folate cycle is a pertinent example of how nutrition has benefited from ODE systems modelling.…”
mentioning
confidence: 99%